On the Performance Analysis of Different Selecting Strategies for Type-II Codebook - Fu, Xiaotian; Ruyet, Didier Le; Visoz, Raphael; Clessienne, Thierry (European Conference on Networks and Communications (Online), 2022)
The Type-II codebook is standardized in recent 5G new radio (NR) physical layer release, which supports high resolution channel state information feedback for MIMO transmission. In this paper, we focus on selecting strategies for rank2 Type-II precoder matrix. Firstly, We extend a rank1 solution in the literature to rank2 which is referred to approach1. This approach is subject to its prerequisite which wastes certain feedback bits. To further exploit the feedback bits, we proposed a new selecting strategy, named approach2. Besides, we illustrate that the subband scalar quantization restricted by the standard deteriorates both the orthogonality and the beamforming gains of the rank2 precoder matrices which has varying influence on approaches. Lastly, the simulation results show that the approach2 is more efficient than the approach1 in high and medium correlation channel cases, which is the opposite in the low correlation case.